Literatur Review : Analisis Pergantian Auditor, Opini Audit, Dan Audit Fee Terhadap Audit Delay - Risma Indah Islami; Afina Khusna Mufidah; Harviyani Azzahra; Alisha Zahra Meiriani; Herlina Manurung (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
Audit delay is the period from the end of the financial year to the date of the company's audit report. There are several factors that influence audit delays, such as change of auditors, audit opinions, and audit fees. The purpose of this study is to analyze the impact of Auditor Change, Audit Opinion, and Audit Fee on Delayed Audit. This research is a Systematic Review study where the method uses review, expression, structured evaluation, classification, and categorization of previously generated evidence based. The article in this study is downloaded from an online application namely google scholar with specific inclusion standards and exclusion criteria. The results of this study showed that the change of auditors would affect the audit delay, the audit opinion influenced the delayed audit, and the audit fee had no influence on the delays audit.